Implications for deriving regional fossil fuel CO2 estimates from atmospheric observations in a hot spot of nuclear power plant 14CO2 emissions - Vogel, Felix; Levin, Ingeborg; Worthy, Doug E. J. (Radiocarbon, 2013)
Using Δ14C observations to infer the local concentration excess of CO2 due to the burning of fossil fuels (ΔFFCO2) is a promising technique to monitor anthropogenic CO2 emissions. A recent study showed that 14CO2 emissions from the nuclear industry can significantly alter the local atmospheric 14CO2 concentration and thus mask the Δ14C depletion due to ΔFFCO2. In this study, we investigate the relevance of this effect for the vicinity of Toronto, Canada, a hot spot of anthropogenic 14CO2 emissions. Comparing the measured emissions from local power plants to a global emission inventory highlighted significant deviations on interannual timescales. Although the previously assumed emission factor of 1.6 TBq(GWa)-1 agrees with the observed long-term average for all CANDU reactors of 1.50 ± 0.18 TBq(GWa)-1. This power-based parameterization neglects the different emission ratios for individual reactors, which range from 3.4 ± 0.82 to 0.65 ± 0.09 TBq(GWa)-1. This causes a mean difference of-14% in 14CO2 concentrations in our simulations at our observational site in Egbert, Canada. On an annual time basis, this additional 14CO2 masks the equivalent of 27-82% of the total annual FFCO2 offset. A pseudo-data experiment suggests that the interannual variability in the masked fraction may cause spurious trends in the ΔFFCO2 estimates of the order of 30% from 2006-2010. In addition, a comparison of the modeled Δ14C levels with our observational time series from 2008-2010 underlines that incorporating the best available 14CO2 emissions significantly increases the agreement. There were also short periods with significant observed Δ14C offsets, which were found to be linked with maintenance periods conducted on these nuclear reactors.